Electroresponsive nanoparticles for drug delivery on demand. Issue 17 (18th April 2016) - Samanta, Devleena; Hosseini-Nassab, Niloufar; Zare, Richard N.
Abstract : An electrically controlled general drug delivery system is reported which can release both small molecule drugs and large peptide hormones. Abstract : The potential of electroresponsive conducting polymer nanoparticles to be used as general drug delivery systems that allow electrically pulsed, linearly scalable, and on demand release of incorporated drugs is demonstrated. As examples, facile release from polypyrrole nanoparticles is shown for fluorescein, a highly water-soluble model compound, piroxicam, a lipophilic small molecule drug, and insulin, a large hydrophilic peptide hormone. The drug loading is about 13 wt% and release is accomplished in a few seconds by applying a weak constant current or voltage. To identify the parameters that should be finely tuned to tailor the carrier system for the release of the therapeutic molecule of interest, a systematic study of the factors that affect drug delivery is performed, using fluorescein as a model compound. The parameters studied include current, time, voltage, pH, temperature, particle concentration, and ionic strength. Results indicate that there are several degrees of freedom that can be optimized for efficient drug delivery. The ability to modulate linearly drug release from conducting polymers with the applied stimulus can be utilized to design programmable and minimally invasive drug delivery devices.